Pengaruh Konsentrasi Nutrisi AB Mix yang Berbeda terhadap Pertumbuhan dan Produksi Dua Varietas Selada (Lactuca sativa L.) Hidroponik Sistem NFT - Sholeh, Wirdaniatus; Sri Wahyuni, Endang (JURNAL AGROPLANT, 2023)
This study aims to determine the concentration of nutrients AB mix liquid biological fertilizer combination will affect the growth and production of three varieties of mustard hydroponic DFT system. This research was conducted at Bedadung Indah AA8 Housing, Jl. Teuku Umar, Tegal Besar Village, Kaliwates District, Jember Regency, which will be held from January 1, 2022 to February 23, 2022 at an altitude of ±89 meters above sea level. This research was conducted using a factorial 2 x 3 Completely Randomized Design (CRD) with 5 replications. The first factor is nutrition (N) consisting of two levels of treatment, nutrient concentration AB mix 1000 ppm (N1) and nutrient concentration AB mix 1000 ppm combination of liquid biological fertilizer 2 ml/lt water (N2). The second factor was variety (V) which consisted of three levels of treatment, Pagoda mustard (V1), mustard green (V2) and mustard kailan (V3). The data obtained were then analyzed by uij F using the help of IBM SPSS Statistic 26 software for Windows, the significantly different results were further tested with Duncan at a level of 0.05. The results showed that the nutrient concentration of AB mix 1000 ppm with a combination of 2 ml/lt water (N2) liquid biological fertilizer gave the best response to the number of leaves and the fresh weight of mustard greens.. The interaction of nutrient concentration of AB mix and its combination with liquid biological fertilizer (N) and variety treatment (V) was not significantly different on the growth and production of three hydroponic mustard varieties using the DFT system.